NLRP3 Inflammasome—A Key Player in Antiviral Responses - Zhao, Chunyuan; Zhao, Wei (Frontiers in Immunology, 2020)
NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome, contains NOD like receptor NLRP3, adaptor ASC and caspase-1, is crucial for host to defense against microbes by promoting IL-1β and IL-18 secretion, and inducing pyroptosis. Following recognizing a variety of pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs) during viral replication, NLRP3 inflammasome is activated and plays fundamental roles in controlling viral infection. Meanwhile, multiple viruses have enveloped elaborate immune evasion strategies by targeting NLRP3 inflammasome. In this review, we will focus on the mechanisms of NLRP3 inflammasome activation during viral infection, as well as the immune escape of viruses by modulating NLRP3 inflammasome activity.